Fish assemblages cope with ocean acidification in a shallow volcanic CO2 vent benefiting from an adjacent recovery area. (May 2020) - Mirasole, Alice; Signa, Geraldina; Gianguzza, Paola; Bonaviri, Chiara; Mazzola, Antonio; Vizzini, Salvatrice
Abstract: Shallow CO2 vents are used to test ecological hypotheses about the effects of ocean acidification (OA). Here, we studied fish assemblages associated with Cymodocea nodosa meadows exposed to high p CO2 /low pH conditions at a natural CO2 vent in the Mediterranean Sea. Using underwater visual census, we assessed fish community structure and biodiversity in a low pH site (close to the CO2 vent), a close control site and a far control site, hypothesising a decline in biodiversity and a homogenization of fish assemblages under OA conditions. Our findings revealed that fish diversity did not show a unique spatial pattern, or even significant relationships with pH, but correlated with seagrass leaf canopy. Among-site similarity was found in the abundance of juveniles, contrary to the expected impacts of OA on early life stages. However, pH seems an important driver in structuring fish assemblage in the low pH site, despite its high similarity with the close control site. This unexpected pattern may represent a combined response of fish mobility, enhanced food resources in the acidified site, and a 'recovery area' effect of the adjacent control site. Highlights: pH played a role in shaping nekto-benthic fish assemblages. Fish diversity did not show unique spatial patterns or significant pH-relations. Species richness and abundance correlated with seagrass canopy, regardless of pH. Unexpected among-site similarity was found in the abundance of juveniles. The area close to low pH site seems to work as a recovery area for fish.